Human CD56dimCD16dim Cells As an Individualized Natural Killer Cell Subset - Amand, Mathieu; Iserentant, Gilles; Poli, Aurélie; Sleiman, Marwan; Fievez, Virginie; Sanchez, Isaura Pilar; Sauvageot, Nicolas; Michel, Tatiana; Aouali, Nasséra; Janji, Bassam; Trujillo-Vargas, Claudia Milena; Seguin-Devaux, Carole; et al. (Frontiers in Immunology, 2017)
Human natural killer cells can be subdivided in several subpopulations on the basis of the relative expression of the adhesion molecule CD56 and the activating receptor CD16. Whereas blood CD56brightCD16dim/- natural killer cells are classically viewed as immature precursors and cytokine producers, the larger CD56dimCD16bright subset is considered as the most cytotoxic one. In peripheral blood of healthy donors, we noticed the existence of a population of CD56dimCD16dim natural killer cells that was frequently higher in number than the CD56bright subsets and even expanded in occasional control donors but also in transporter associated with antigen processing-deficient patients, two familial haemophagocytic lymphohistiocytosis type II patients, and several common variable immunodeficiency patients. This population was detected but globally reduced in a longitudinal cohort of 18 HIV-1-infected individuals. Phenotypically, the new subset contained a high percentage of relatively immature cells, as reflected by a significantly stronger representation of NKG2A+ and CD57- cells compared to their CD56dimCD16bright counterparts. The phenotype of the CD56dimCD16dim population was differentially affected by HIV-1 infection as compared to the other NK cell subsets and only partly restored to normal by antiretroviral therapy. From the functional point of view, sorted CD56dimCD16dim cells degranulated more than CD56dimCD16bright cells but less than CD56dimCD16- NK cells. The population was also identified in various organs of immunodeficient mice with a human immune system (“humanized” mice) reconstituted from human cord blood stem cells. In conclusion, the CD56dimCD16dim NK cell subpopulation displays distinct phenotypic and functional features. It remains to be clarified if these cells are the immediate precursors of the CD56dimCD16bright subset or placed somewhere else in the NK cell differentiation and maturation pathway.